INFLUENCE INFLUENCE OF SECURITY MANAGEMENT MECHANISM IN ADDRESSING EMERGING BODA-BODA SECURITY THREATS IN CHANGAMWE SUB-COUNTY, MOMBASA COUNTY, KENYA - Limo, Jerry (Advances in Social Sciences Research Journal, 2022)
This paper uses data collected for an MA Thesis on the influence of security management mechanism in addressing emerging Boda-Boda security threats in Changamwe Sub-County in Mombasa County, Kenya. The study has been necessitated by the conception that management of Boda-Boda security threats will significantly lower Annual crime patterns like terror attacks, kidnappings, robberies, target violent crimes among others. According to this study, the sector operated without proper regulation and or control. The study was guided by three specific objectives; to establish the types of emerging Boda-Boda security threats prevalent in Changamwe Sub-County, to examine perceptions of security personnel on emerging Boda-Boda security threats, and to establish security management mechanism adopted by security personnel in addressing Boda-Boda Security threats in Changamwe Sub-County in Mombasa County. This study was focused by crime pattern and Routine Activity Theory. The study comprised of 144 respondents. Stratified random sampling method and purposive sampling techniques were used to select respondents and descriptive statistics used in data analysis. According to the study, the main types of Boda-Boda related crimes prevalent in Changamwe Sub-County were robberies, thefts, kidnappings, murders and other forms of gun violence. One of the major perceptions of emerging security threat is that of motor bike related gang that has increased vulnerability of many businesses and targets due to their disguised surveillance on unsuspecting victims and targets. According to the study Boda-Boda related crimes are largely under regulated. As one of the major policy concerns, concerted efforts by the Government and the Private sector to come up with preventive social programmes such as economic empowerment and alcohol and drug control programmes that will potentially avert the identified pushing factors responsible for rampant Boda-Boda sector related crimes; Poverty and alcohol consumption and drug use. Social programmes may also come up with mechanisms of social justice to supplement government enforcement mechanisms. Finally, National Police Service should increase intelligence and surveillance of the sub-sector to identify crime patterns, trends and hot spots in order to cut this problem at the nib.